THE ROLE OF PERSONNEL IN ASSESSING THE COMPETITIVENESS OF BUSINESS ENTITIES - Попадинець, Ірина; Андрусів, Уляна; Данилюк, Микола; Бойчук, Олексій (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article proposes a comprehensive methodological approach to assessing the role of personnel in the competitiveness of the entity, which is structured in four blocks: methodology - defining the purpose, determining internal and external factors of staff efficiency (SWOT-analysis), functional-cost analysis of personnel management; information support involves the collection of information and the formation of an information base for evaluating the personnel of the business entity, the formation of the author’s questionnaire, espresso evaluation, the formation of an expert group; monitoring involves the use of sound tools, methods and technologies for evaluating the personnel of the entity (calculation of performance indicators of personnel, espresso assessment of personnel and assessment of job satisfaction) and reserves for its improvement; interpretation of the results is to form conclusions based on the interpretation of the competitiveness polygon of the entity. The main components of the personnel policy of the business entity are detailed: the policy of recruitment, selection and placement of personnel; policy of career guidance, adaptation and professional development; employment policy; career growth management policy; incentive policy; social policy. It is proposed to assess the level of competitiveness of the entity depending on the impact of staff on it, based on the main subsystems of the entity: subsystem for forming the labor potential of the entity, subsystem for managing the quality of working life, subsystem for managing labor potential. management and subsystem of labor potential management. It is proved that the management of the implementation strategy of the personnel development of the entity depends on the functions that ensure its effectiveness. Therefore, the analysis of the flow of management functions on the implementation of the strategy of personnel development of the entity is proposed.